POLA SPASIAL PERMUKIMAN SUKU BAJO DI TOROSIAJE LAUT, PROVINSI GORONTALO - , Satar Saman,ST ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bajau sea Torosiaje Village has its own uniqueness which settlements are built on the sea is completely separate from the mainland, closeness is evident in 1982 when the government attempted to relocate the residents housed Bajo for the given piece of land to grow crops, but they do not feel at home and one by one the members of this tribe left the relocation sites and back to the sea. Torosiaje Village neighborhood is a traditional settlement with a model house on stilts. Torosiaje village sea is generally populated by people who are still concerned family and involve family members in the process of making the house, forming a clustered settlements in the coastal marine waters. The process of the development of these settlements grow spontaneously with practical technical and simple and does not eliminate the influence of marine culture lifestyle residents to date. Torosiaje Bajo on this until now, can not be separated from geography and natural environment areas in background background by residents' daily activities as fishermen / sailors The purpose of the study to examine the spatial patterns of settlement in the village of Bajo Torosiaje sea, knowing how spatial patterns that exist in the current sea Torosiaje village with an ethnic look Bajo tribe that lived in the sea which can not be separated from the sea. Data collection methods such as observation made using the rationalistic approach and processed data are descriptive. The development of spatial pattern is influenced by a number of factors, such as physical and natural, socio-cultural, economic, government regulations. The spatial pattern of village settlement Torosiaje sea views from natural factors formed by geographical sea bridge that connects to homes, building mass and open ocean areas. The influence of sea culture in shaping spatial patterns are shown in the pattern-forming elements such as presence of the floating markets, residential floating, floating infrastructure The factors that influence the development of spatial pattern in marine Torosiaje Bajo in the region just as the sea is geography, physical settlement, socio-cultural and economic. Standard rules of settlement affect the site layout of the house, which follows the coastline and form a linear pattern of settlement areas, in addition to the bridge system, which connects to the homes. For it can be shown that the mass of the building (Solid) and open space (Void) also affects the spatial patterns of settlement in the village of Bajo Torosiaje sea. Patterns in the ocean Torosiaje village shows that the pattern formed from linear and organic patterns. It can be concluded that changes in the function of an area will affect the pattern. The pattern formed any cultural, geographic, economic, natural and physical factors, government regulations, building mass and open space.